The governance of large technical systems - Coutard, Olivier, 1965- (London ; New York : Routledge, 1999)
This work examines the governance of large technical systems (LTS) at firm, imdustry and state levels and the interactions between the systems and society. In particular, international contributors explore the implications of major technological, economic and social changes during the last twenty years for traditional forms of LTS governance. Their research is centred around the following themes:* traditional forms of governance* new regulatory challenges* the governability of complex technologies* conceptual issues related to the governance of inter-organizational networks<BR.
Introduction : the evolving forms of governance of large technical systems / Olivier Coutard -- Transforming an energy system : the evolution of the manufactured gas industry and the transition to natural gas in the United States (1807-1954) / Joel A. Tarr -- Striking bonanza : the establishment of a natural gas regime in the Netherlands / Arne Kaijser -- Technical systems and strategy : intercontinental telecommunications in the first quarter of the twentieth century / Pascal Griset -- Designing and operating storm water drain systems : empirical findings and conceptual developments / Konstantinos Chatzis -- Power plays : the politics of interlinking systems / Jane Summerton -- From control to coordination : new governance models for information networks and other large technical systems / Janet Abbate -- The internationalization of large technical systems : dynamics of change and challenges to regulation in electricity and telecommunications / Francis McGowan -- Splintering networks : the social, spatial and environmental implications of the privatization and liberalization of utilities in Britain / Simon Guy, Stephen Graham and Simon Marvin -- Theories of technology and the abolition of nuclear weapons / Donald MacKenzie -- Some theoretical and critical remarks on the air transportation system and other large technical systems / Alain Gras -- Are there such things as small networks? / Jean-Marc Offner -- On control and shifting boundaries : modern society in the web of systems and networks / Reiner Grundmann -- High variability discourse in the history and sociology of large technical systems / Bernward Joerges.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Public utilities -- Management; Transportation -- Management; Telecommunication -- Management; Corporate governance; Services publics -- Gestion; Transport -- Gestion; Télécommunications -- Gestion; Gouvernement d'entreprise.; SOCIAL SCIENCE -- General; BUSINESS & ECONOMICS -- Infrastructure; Corporate governance; Public utilities -- Management; Telecommunication -- Management; Transportation -- Management